Organizational Commitment as Mediator Between Administrative Creativity and Job Performance among Department Managers at Al Hussein Bin Talal University - Alleimoun, Audeh; Ola Allaymoun, Ola; Twaissi, Naseem. M.; Alhawtmeh, Omar M.; Othman, Mohamad Rosni; Maqbool, Muath (Manunggal Halim Jaya, 2024)
The study examines the impact of organizational commitment on administrative creativity and job performance among department managers at Al Hussein bin Talal University. Job performance refers to managers' ability to accomplish their duties efficiently and effectively. Administrative creativity refers to managers' ability to generate innovative ideas and solutions. Organizational commitment is loyalty to an organization. Quantitative research will be used in the study. Surveys will be distributed to Al Hussein bin Talal University department managers to collect data. The study will use validated measures of administrative creativity, organizational commitment, and job performance. Statistical analyses will be performed to examine the relationships and mediating effects among the variables, such as correlation analysis and mediation analysis. This study will impact human resource management and organizational development practices at Al Hussein bin Talal University. The university can improve department manager performance by fostering a culture that encourages innovation and administrative creativity. In addition, understanding organizational commitment can improve employee commitment to the organization.